Willingness to Comply With Biosecurity in Livestock Facilities: Evidence From Experimental Simulations - Merrill, Scott C.; Moegenburg, Susan; Koliba, Christopher J.; Zia, Asim; Trinity, Luke; Clark, Eric; Bucini, Gabriela; Wiltshire, Serge; Sellnow, Timothy; Sellnow, Deanna; Smith, Julia M. (Frontiers in Veterinary Science, 2019)
Disease in U.S. animal livestock industries annually costs over a billion dollars. Adoption and compliance with biosecurity practices is necessary to successfully reduce the risk of disease introduction or spread. Yet, a variety of human behaviors, such as the urge to minimize time costs, may induce non-compliance with biosecurity practices. Utilizing a “serious gaming” approach, we examine the how information about infection risk impacts compliance with biosecurity practices. We sought to understand how simulated environments affected compliance behavior with treatments that varied using three factors: 1) The risk of acquiring an infection, 2) the delivery method of the infection risk message (numerical, linguistic and graphical), and 3) by the certainty of the infection risk information. Here we show that compliance is influenced by message delivery methodology, with numeric, linguistic, and graphical messages showing increasing efficacy, respectively. Moreover, increased situational uncertainty and increased risk were correlated with increases in compliance behavior. These results provide insight towards developing messages that are more effective and provide tools that will allow managers of livestock facilities and policy makers to nudge behavior towards more disease resilient systems via greater compliance with biosecurity practices.